PATERNALISTIC LEADERSHIP ON GEN-Y EMPLOYEES'TURNOVER INTENTIONS WITH MOTIVATION AND SATISFACTION AS A MEDIATOR - Nurcahyanto, Didik; Rofiaty, Rofiaty; Rahayu, Mintarti (Jurnal Aplikasi Manajemen, 2018)
This study examines the effect of paternalistic leadership on Gen-Y employees'turnover intentions, mediated by motivation and satisfaction. The research used 186 samples of Gen-Y employees from BCA Regional Office, Malang as respondents. Research data were obtained through questionnaires and analyzed through SmartPLS. The results indicate that paternalistic leadership affects Gen-Yemployees'turnover intentions through satisfaction.Mediation effect of motivation is not found in the influence of paternalistic leadership on turnover intention.The implementation of paternalistic leadership cannot keep turnover rate low, but only to help.